We need two things to write the recursive formula
[tex]a[/tex] is the first value of this sequence. For this set of values, [tex]a = 1[/tex], since [tex]1[/tex] appears first.
[tex]d[/tex], the common difference, is [tex]d = t_{3} - t_{2} = t_{2} - t_{1}[/tex]. Basically it's just the the higher term minus the previous terms. To solve for [tex]d[/tex],
So regardless of what terms you choose, the common difference will be the same. Now the general formula for a recursive function is
where [tex]n[/tex] is the [tex]nth[/tex] term. Let's substitute for [tex]a[/tex] and [tex]d[/tex] in this formula.
[tex]t_{n} = 1 + (n - 1) \times -3\\t_{n} = 1 + -3(n - 1)\\t_{n} = 1 - 3(n - 1)[/tex]
So the recursive formula is [tex]t_{n} = 1 - 3(n -1)[/tex]